GENDER DYSPHORIA AS SEEN IN NORMAL MOVIE - Arsy Ramadhani; Dwi Budi Setiawan (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2021)
In society gender is a norm of someone’s behavior, gender also show the someone’s sexual orientation in their life, however in our society we just know gender is only divided in to two, which is female and male, and we did not realized that there are a lot of kind of gender in diversity. The norm is reflected to culture and behavior of society in daily activities and affect to someone’s perspective towards gender cases, Thus, the researcher aims to the reader can see the existence of gender dysphoria in society and accept them as part of human. This study focuses on Normal Movie by Jane Anderson. In analayzing the data, the researcher uses Gender Trouble theory by Judith Butler. Furthermore, this study uses qualitative descriptive; thus, the researcher analyzes the data critically.The result of this researchr shows that there are some characteristic and actions from the character which can identified as part of gender dysphoria.